SLE classification criteria: Science-based icons or algorithmic distractions – an intellectually demanding dilemma - Rekvig, Ole Petter (Frontiers in Immunology, 2022)
It is, so to say, not a prerogative authority assigned to SLE classification criteria that allow them to declare something definitively important about SLE. This is particularly true as criteria-based classification processes overrule the highly needed evolution of concise diagnostic criteria. It is classification criteria that allocate SLE patients into cohorts intended to describe the nature of their disease. Therefore, all major SLE classification criteria since the 1971 preliminary criteria usurp the role of diagnostic criteria. Today´s practice silently accept that the SLE classification process “diagnose” SLE patients despite the fact that classification criteria are not accepted as diagnostic criteria! This is a central paradox in contemporary SLE research strategies. Contemporary SLE cohorts are designed to investigate SLE´s etiological features. However, each cohort that is categorized by classification criteria has one central inherent problem. From theoretical and practical arguments, they embody multiple distinct clinical phenotypes. This raises the critical and principal question if phenotypically heterogenic SLE cohorts are useful to identify basic SLE-specific etiology(ies) and disease process(es). In times to come, we must prioritize development of firm diagnostic criteria for SLE, as the classification criteria have not contributed to reduce the enigmatic character of the syndrome. No radical improvements are visible in the horizon that may lead to concise investigations of SLE in well-defined homogenous SLE cohorts. We must develop new strategies where studies of phenotypically standardized cohorts of SLE must be central elements. Problems related to contemporary SLE classification criteria are contemplated, analyzed, and critically discussed in this study.